Plan para el adecuado manejo de sedimentos, que permite incrementar la vida útil del embalse la esmeralda (2018)
Accumulation of sediments in the dams is one of the problematic ones that afict more to the hydroelectric power stations. The transported sediments can arrive to obstruct the mouths of taking in the prey and to generate abrasive effects in the turbines of generation, their components of operation and the structures of concrete (Yearling calf, Alarcón, Salavarrieta, & Fuquen, 2015). In recent forums and academic investigations, the management of sediments like the challenge immediate to being faced by the generators around the world has been emphasized (Sanchez & Fuquen, 2013). Colombia is not other people's to this problem, whereas clause that it has near 11000 MW of capacity installed in hydroelectric generation. This work not only serves like example for hydroelectric at world-wide level, but it establishes a landmark in history for handling of dams in the country and the continent. In this article a summary becomes of the plan of action executed from year 2016, as it leaves from the strategy drawn up by AES Chivor for the suitable management of sediments in the dam. Applying the Plan of Handling of Sediments - PMS will be allowed to extend the life utility of the project like minimum other 50 years (until year 2070), and that will allow to maintain the EBITDA of the company during the anticipated additional period of operation.